**Q 1.**What replaces the question mark?

4 + 7 + 2 = 281435

7 + 3 + 9 = 212781

6 + 2 + 7 = 121456

2 + 8 + 5 = 164036

8 + 4 + 6 =

**?**

**Answers:**8 + 4 + 6

(8
* 4) = 32 and (4 * 6) = 24. Now putting the values together it gives 3224.

Now (8 – 1) = 7. If we put the digit together
with 3224, it gives 32247.

Now (8 + 4 + 6) + 2 = 20 and now taking the
last digit of the number ’20’ and keeping together with the number 32247, the
final number ‘322470’ is ready.

**Q 2.**What replaces the question mark?

56
3 49 27 18

74
62 19 8 35

65
92

**?**34 81**Answer:**For equation (iii), we need to get the sum value equal to 45.

So
the logic should be (6 + 5 + 9 + 2 + ? + 3 + 4 + 8 + 1) = 45.

Then,
38 + ? = 45

So
? = (45 – 38) = 7

So
? = 7.

**Q 3.**What replaces the question mark?

5
+ 3 + 2 = 151022

9
+ 2 + 4 = 183652

8
+ 6 + 3 = 482466

5
+ 4 + 5 = 202541

Then,
7 + 2 + 5 =

**?**

**Answer:**It works out to be a + b + c = (a * b) (a * c)??

The
last 2 digit is equal to (a * b) + (a * c) - b

We
use the same formula;

(a
x b) = (7×2) = 14;

(a
x c) = (7*5) = 35;

(a
* b) + (a*c)-b = (7 × 2) + (7 × 5) - 2 = 14 + 35 - 2 = 47

Hence
7 + 2 + 5 = 143547

**Q 4:**What replaces the question mark?

10×11×12=9

11×12×13=9

12×13×14=9

13×14×15=9

Then
14×16×20=

**?****Answer:**10 × 11 × 12 = {(1+0) × (1+1) × (1+2)}² =6^2= 36 = 3 + 6 = 9.

11
× 12 × 13 = {(1 + 1) × (1 + 2) × (1 + 3)}² = 24^2 = (2 + 4)² = 36 = 3 + 6 = 9.

12
× 13 × 14 = {(1 + 2) × (1 + 3) × (1 + 4)}² = 60^2 = (6 + 0)² = 36 = 3 + 6 = 9.

13
× 14 × 15 = {(1 + 3) × (1 + 4) × (1 + 5)}² = 120^2 = (1 + 2 + 0)² = 9.

14 × 16 × 20 = {(1 + 4) × (1 + 6) (2 + 0)}² = 70^2 = (7 + 0)² = 49 = 4 + 9 = 13 =
1 + 3 = 4.